1987
DOI: 10.1520/gtj10545j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic High Stress Experiments on Soil

Abstract: The split-Hopkinson pressure bar (SHPB) technique has been adapted to measure the dynamic response of soil to impulse loads. The experimental technique is relatively simple and can investigate soil response in regimes beyond the capabilities of current equipment used for dynamic soil laboratory investigations. Soils have several characteristics that must be considered in designing a SHPB experiment and evaluating the data (for example, low wave speeds, nonlinear hysteretic behavior, and low unconfined compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…For example, results have been reported on the effect of unsaturated water levels on silica sand [5], on the mechanical behavior of soft soil [6], clayey/silty soil [7] and dry sand [8] under confinement, and effect of moisture on sand mechanical properties [9] at relatively low compressive stress levels, as well as the mechanical behavior of dry sand under single pulse loading [10]. For dense sand under initial loading, its mechanical impedance is low.…”
Section: Introductionmentioning
confidence: 99%
“…For example, results have been reported on the effect of unsaturated water levels on silica sand [5], on the mechanical behavior of soft soil [6], clayey/silty soil [7] and dry sand [8] under confinement, and effect of moisture on sand mechanical properties [9] at relatively low compressive stress levels, as well as the mechanical behavior of dry sand under single pulse loading [10]. For dense sand under initial loading, its mechanical impedance is low.…”
Section: Introductionmentioning
confidence: 99%
“…The issue was considered by some users of the SHPB [10,12,13] who concluded that the frequency content of their signals was such that ignoring the non-uniform bar response had a negligible effect on the accuracy of their results. Safford [14] appears to have been the first to propose including a correction for the non-uniform bar response to experimental HPB signals.…”
Section: Distortion Of Hopkinson Pressure Bar Signalsmentioning
confidence: 99%
“…However, while the phase-shift dispersion effect has been widely recognized, the non-uniform bar response aspect of the theory has received surprisingly little attention in subsequent HPB research. The issue was considered by some users of the SHPB [10,12,13] who concluded that the frequency content of their signals was such that ignoring the non-uniform bar response had a negligible effect on the accuracy of their results. Safford [14] appears to have been the first to propose including a correction for the non-uniform bar response to experimental HPB signals.…”
Section: Distortion Of Hopkinson Pressure Bar Signalsmentioning
confidence: 99%
“…For many years, the unflagging interest and continuous development in the field of testing the mechanical properties of various building materials subjected to dynamic effects stresses have been noticed [1]. Particularly significant increase in the number of publications in this field concerns metals as well as for concretes [2], polymers, wood and soils [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Indeed, a large part of engineering problems includes research into high-rate strain-stress (HSR) soil response.…”
Section: Introductionmentioning
confidence: 99%